1977
DOI: 10.1111/j.1432-1033.1977.tb11843.x
|View full text |Cite
|
Sign up to set email alerts
|

The Modification of Nuclear Proteins by ADP‐ribosylation

Abstract: When incubated in vitro purified mouse nuclei incorporate NAD into poly(ADP-Rib). Analysis of the product on CsCl/urea gradients showed that a large proportion of the poly(ADP-Rib) was not attached to protein. The free poly(ADP-Rib) did not appear to arise through degradation and its chain length was significantly longer than the poly(ADP-Rib) attached to proteins. Fractionation of the proteins on hydroxyapatite revealed that tissue-specific modification of both the histones and non-histone proteins, had occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…are known to be modified by covalent attachment of poly(ADP-ribose) Enzymic regulation by poly(ADP-ribosyl)ation Tanaka et al, 1984; Jongstra-Bilen et al., 1983;Kawaichi et al, 1981 Rickwood et al (1977) Adamietz (1982) Adamietz ( (1984) require DNA for activity, it has been suggested that inhibition is due to an electrostatic repulsion between the natural substrate, DNA, and the ADP-ribose chains covalently bound to the enzymes Ferro & Olivera, 1982. Evidence to support this hypothesis is provided by the findings that ADP-ribosylated endonuclease and ADPRT have a reduced affinity for DNA, that free poly(ADP-ribose) is noninhibitory, and that positively charged DNAbinding proteins enhance endonuclease activity Ferro & Olivera, 1982).…”
Section: Poly(adp-ribose) Acceptor Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…are known to be modified by covalent attachment of poly(ADP-ribose) Enzymic regulation by poly(ADP-ribosyl)ation Tanaka et al, 1984; Jongstra-Bilen et al., 1983;Kawaichi et al, 1981 Rickwood et al (1977) Adamietz (1982) Adamietz ( (1984) require DNA for activity, it has been suggested that inhibition is due to an electrostatic repulsion between the natural substrate, DNA, and the ADP-ribose chains covalently bound to the enzymes Ferro & Olivera, 1982. Evidence to support this hypothesis is provided by the findings that ADP-ribosylated endonuclease and ADPRT have a reduced affinity for DNA, that free poly(ADP-ribose) is noninhibitory, and that positively charged DNAbinding proteins enhance endonuclease activity Ferro & Olivera, 1982).…”
Section: Poly(adp-ribose) Acceptor Proteinsmentioning
confidence: 99%
“…2a) shows the formation of free (ADP-ribose)n chains, not linked to protein (Rickwood et al, 1977;Benjamin & Gill, 1980a). Whether these truly occur in vivo, or are artifacts produced by cleavage of ADP-ribose residues from proteins during experimental handling of tissues, is still a matter of contention.…”
Section: Introductionmentioning
confidence: 99%
“…The preferential ADP-ribosylation of histone H2B in rat liver nuclei and of histone Hl in rat brain nuclei has been demonstrated [7,9]. These findings suggest a tissue specific ADP-ribosylation of histones.…”
Section: Resultsmentioning
confidence: 94%
“…In rat liver or mouse liver nuclei, histone HZB was the major acceptor of ADPR [7]. In contrast in HeLa cell nuclei [8], rat brain nuclei or M2 cell nuclei [9], histone Hl showed the highest incorporation of ADPR. On this basis it was suggested that histone or nonhistone nuclear protein ADP-ribosylatiori may play an important role in cell differentiation or gene expression,…”
Section: Introductionmentioning
confidence: 99%
“…A broader study of poly(ADP-ribosy1)ation has been presented by Rickwood et al ( 1977). [32PlADP-ribosylated proteins were separated from nucleic acids by CsCI-equilibriumdensity-gradient centrifugation, fractionated on hydroxyapatite and subjected to two-dimensional gel electrophoresis.…”
mentioning
confidence: 99%